Characterizing and exploring the implications of maritime irregular warfare - Dunigan, Molly (Rand Corporation monograph series., 2012)
An assessment of the maritime component of a series of historical and ongoing operations reveals that current notions of irregular warfare would benefit from increased recognition of potential maritime contributions to such campaigns.